Pengaruh Pembiayaan Mudharabah Terhadap Perkembangan Usaha Mikro Kecil Menengah (UMKM) di BMT Baiturrahman Bojong Gede - Ramon Ramadhan (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
This study conducted observations and studies to determine the effect of mudharabah financing provided by BMT Baiturrahman on the development of Micro, Small and Medium Enterprises (MSMEs). The research technique used in this study is a quantitative technique with a population of customers who take financing in the BMT with a total of 166 customers financing after using the 10% Slovin error formula to 63 customers as the sample. The sampling technique in this study uses non-probability sampling by convenience sampling method. Whereas for data analysis methods using a simple linear regression analysis model, and for processing data using SPSS 23. This study concluded that mudharabah financing has a very strong relationship (correlation) which is very significant for the development of MSMEs. So it can be concluded that mudharabah financing has a significant effect on the development of MSMEs.